Analysis of the Effectiveness of Online Learning in the Middle of the Covid-19 Outbreak - Haniaturizqia; Rifa, Nafisatu (Proceeding International Conference on Science and Engineering, 2021)
Abstract: The Covid-19 pandemic has disrupted the conventional learning process, thus affecting the world of education in Indonesia, including the implementation of lectures at the Biology Education Study Program at UIN Sunan Kalijaga Yogyakarta, so a solution is needed to answer these problems. Online learning is an alternative that can overcome this problem in an effort to reduce the spread of Covid-19 in the campus environment. The purpose of this study was to obtain an overview of online learning in the Biology Education Study Program at UIN Sunan Kalijaga Yogyakarta during the Covid-19 pandemic. Data were collected by interview via zoom cloud meeting. Data analysis was performed using interactive analysis techniques Miles & Huberman. The results showed that: (1) online learning has flexibility in its implementation and is able to encourage independent learning and motivation to be more active in learning; (2) students already have the basic facilities needed to take part in online learning; and (3) distance learning encourages the emergence of social distancing behavior and minimizes the appearance of student crowds so that it is considered to reduce the potential for the spread of Covid-19 in tertiary institutions. Weak supervision of students, lack of strong signals in remote areas, and high quota fees are some of the challenges in online learning. Increasing independent learning, interest and motivation, courage to express ideas and questions are other advantages of online learning.